DESAIN MODUL KIMIA BERBASIS KARAKTER UNTUK SISWA SMK DAN MA MATERI STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR - Uswatun Hasanah; Lazulva Lazulva (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
AbstractThe aim of this study is to produce character on chemistry module which is valid and practical. Type of this study is a research and development (R&D) research using Borg and Gall’s study design which covers the potential and problems, data collection, product design, validation design, revision design, and product trials. This study was conducted in Darul Hikmah Islamic High School, Darel Hikmah Vocational High School and Taruna Satria Pekanbaru Vocational High School. The subject of this study is all of the teachers in chemistry subject which consists of five teachers. The object of this study is character-based discipline pillar on chemistry module. The data from questionnaires. The instruments of this study were try-out validity questionnaires and practical questionnaires. The collecting data technique of this study was descriptive analysis technique. The module data was validated with average 88.6% (valid) and data tried-out to five chemistry teachers practicallited was tested with average 87.6% (practical). Based on the result finding, this study could be identified that character-based on chemistry learning is suitable and practical so can be applied for chemistry education especially on atomic structures and periodic components.Keywords: module, character education, atomic structures, periodic components